Paw-paws airborne again? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The Côte d'Ivoire programme for promoting nontraditional exports forecasts that exports of papaya (paw-paw) are set to double, rising from 225 t in 1998 to 500 t in 1999, thanks to cheap cargo charter flights between Yamassoukro and Oostende...